The Analysis of Partnership Patterns in the Coconut Sugar Agroindustry in Manyampa Village Ujung Loe District Bulukumba Regency South Sulawesi Province - Ayu Reski; Haji Saediman; Wa Ode Yusria (Jurnal Ilmiah Membangun Desa dan Pertanian, 2022)
This study aims to determine the pattern of partnerships formed in the coconut sugar agroindustry in Manyampa Village, Ujung Loe District, Bulukumba Regency. This research was carried out in Manyampa, Ujung Loe District, Bulukumba Regency, South Sulawesi Province, from June 2021 to February 2022. The population in this study were all coconut sugar craftsmen who had a partnership relationship with the coconut sugar agro-industry in Manyampa Village, Ujung Loe District, Bulukumba Regency, totalling 14 people. And collectors as partners, namely 1 (one) person. Sampling was carried out using the Non-Probability Sampling technique, namely saturated sampling (Census), so the number of samples in this study amounted to 15. The variables used in this study include the characteristics of the respondents of coconut sugar craftsmen: age, education, business experience, number of tapped coconut trees, and number of family members. Collector traders include age, education, and the number of family members; The partnership pattern includes the background for the formation of the Partnership, the implementation of the Partnership, as well as the rights and obligations of the partnering party. Data analysis used descriptive qualitative analysis. The results showed that the partnership pattern formed in the coconut sugar agro-industry in Manyampa Village, Ujung Loe District, Bulukumba Regency tends to follow the pattern of agribusiness operational cooperation (KOA). The partnership pattern includes the background for the formation of the Partnership, the implementation of the Partnership, as well as the rights and obligations of the partnering party. Data analysis used descriptive qualitative analysis. The results showed that the partnership pattern formed in the coconut sugar agro-industry in Manyampa Village, Ujung Loe District, Bulukumba Regency tends to follow the pattern of agribusiness operational cooperation (KOA). The partnership pattern includes the background for the formation of the Partnership, the implementation of the Partnership, as well as the rights and obligations of the partnering party. Data analysis used descriptive qualitative analysis. The results showed that the partnership pattern formed in the coconut sugar agro-industry in Manyampa Village, Ujung Loe District, Bulukumba Regency tends to follow the pattern of agribusiness operational cooperation (KOA).